2017
DOI: 10.5937/jpea1703174v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed coat colour on the seed quality and initial seedling growth of red clover cultivars (Trifolium pratense)

Abstract: The objective of this study was to investigate the influence of seed coat colour on the seed quality of four red clover cultivars (germination, dormancy (hard seeds) REZIME Cilj istraživanja bio je da se ispita uticaj boje semena četiri sorte crvene deteline proizvedene u Srbiji tokom dve godine na njihov kvalitet (klijanje, dormantnost (tvrdo seme), mrtvo seme i početni porast klijanaca (vigor)). U ovom istraživanju su prvo vizuelno razdvojena semena po boji, a zatim su razdvojena digitalnim kolor separator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…In addition, and contrary to what happened in Phases I and II, significant differences between the morphs were found in the germination parameters in distilled water and NaCl solution, with the yellow morph requiring less or much less time for germination to start and to complete than the light purple morph, while simultaneously attaining higher values of final germination. Such better performance of the yellow morph, which was not observed in Phases I and II, has also been found, with few exceptions [40], in other studies involving a variety of cultivars of red clover [7,14,41], suggesting that seed coat color can be used as a broad correlate of seed germination vigor in red clover.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, and contrary to what happened in Phases I and II, significant differences between the morphs were found in the germination parameters in distilled water and NaCl solution, with the yellow morph requiring less or much less time for germination to start and to complete than the light purple morph, while simultaneously attaining higher values of final germination. Such better performance of the yellow morph, which was not observed in Phases I and II, has also been found, with few exceptions [40], in other studies involving a variety of cultivars of red clover [7,14,41], suggesting that seed coat color can be used as a broad correlate of seed germination vigor in red clover.…”
Section: Discussionsupporting
confidence: 63%
“…In short, the superior performance of the yellow morph in relation to the light purple morph found in germination, which appears to be a trait stable across cultivars in red clover seeds, disappears as plants develop, and turns into a superior performance of the light purple morph in seedling growth. since long in the seeds of red clover [40,41] despite that differences of seed weight might depend on the location within plants of the flowers bearing the seeds [40]. Table A1.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that perennial forage legumes are characterized by the presence of hard-dormant seeds (Zimmermann et al, 1998;Velijević et al, 2017), which is associated with the reduction in germination. The seed coat of hard seeds contains more polyphenols, tannins, and other matters, thus possessing a different anatomical and morphological composition compared to normal seed which readily germinates (Galussi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The yellow-coated seeds had considerably higher germination success rate and growth ability than browncoated seeds in white clover. The results did not consistent to the results found in studies of the cowpea (Marwanto, 2004), pea (Atak et al 2008) and other legumes, which concluded that the darker the colour, the higher the seed vigour (Velijević et al 2017). Several previous researches documented that, delayed harvest could largely decrease seed germination success and subsequent seedling growth, which results from reduction in seed protein percentage (Darby and Lauer, 2002;Gaile, 2008;Sallam and Ibrahim, 2014).…”
Section: Seed Maturity Effectmentioning
confidence: 72%
“…That is, welldeveloped seeds can easily germinate under suitable water conditions and grow into seedlings (Li et al 2013). As the seed matures, its coat changes colour at different developmental stages (Velijević et al 2017). Typically, different coat colours represent variations in seed maturity based on their correlation to water uptake (Ertekin and Kirdar, 2010), gas diffusion (West and Harris, 1963), seed dormancy (Baskin et al 2000) and other characteristics in of Trifolium pratense (Atis et al 2011), Arabidopsis thaliana (Debeajun et al) and Cyamopsis tetragonoloba (Liu et al 2007).…”
Section: Introductionmentioning
confidence: 99%